"Beyond Pain": Health Education about Headaches - Santos, Davi Lopes; Ferreira, Eduarda Lima Verde; Filho, Hildel Freire Leite; Almeida, Miguel Vieira de; Guimarães, Ingred Pimentel; Pereira, Késia Sindy Alves Ferreira; Douberin, Cristina Albuquerque (Headache Medicine, 2023)
Full abstract in PDF.